This Study Compared the Malaria Parasite Intensity in Cases of Mono-Infection and Co-Infection with Typhoid among the Patients Attending Selected Health Facilities in Wukari, Taraba State - John-Zakka U.E; Agere H.I.J; Amos T.J; Ogunmola A.O; Abdulrasheed M.H; Yafriyau E.P (African Journal of Clinical Medicine and Pharmacy Research, 2026)
This study compared malaria parasite intensity in mono-infection and in co-infection with typhoid among febrile patients attending selected health facilities in Wukari, Nigeria. A total of 418 clinically diagnosed febrile patients were enrolled, and from each, blood and stool samples were collected for blood film examination and stool culture, respectively. Overall, 75.3% of malaria-positive cases had low parasite intensity, whereas 24.7% had higher parasite density, with a statistically significant difference (p < 0.001). Among the 83 patients with malaria mono-infection, low-intensity (+) parasitemia was more frequent than high-intensity parasitemia, indicating that uncomplicated malaria is more commonly associated with lower parasite density. In contrast, among co-infected cases, 68.9% of patients with high malaria intensity were co-infected with Salmonella (typhoid), while 31.1% of patients with low malaria intensity were co-infected, with an overall p value < 0.011. The odds ratio of 6.766 indicates that individuals with high malaria intensity have approximately sevenfold higher odds of developing typhoid fever compared to those with low malaria intensity. These findings suggest that elevated malaria parasite density is strongly associated with typhoid co-infection and underscore the need for healthcare providers to maintain heightened vigilance for severe malaria presentations in patients with concurrent typhoid infection. The study concludes that a comprehensive control program targeting vector breeding sites and improving sanitation and public health education is essential to reduce the burden of malaria–typhoid co-infection in the study area.